Dear Mr. Henshaw - Cleary, Beverly; Zelinsky, Paul O. (New York : Avon, 1983)
In his letters to his favorite author, ten-year-old Leigh reveals his problems in coping with his parents' divorce, being the new boy in school, and generally finding his own place in the world.
3-6
Newbery Medal/Honor, 1995
3-6
Wilson's Junior High School
Newbery Medal/Honor
Horn Book
Keywords: Schools -- Fiction; Divorce -- Fiction; Parent and child -- Fiction; Divorce -- Fiction; Parent and child -- Fiction; School stories